(untitled) (Bangladesh Journal of Agricultural Research, 2016)
A field experiment was conducted on a saline environment of Shatkhira to assess the feasibility of an intensive wheat-maize-rice cropping system with crop residue used as mulch, bed planting and fertilizer management to improve productivity. Three levels of fertilizers (Recommended dose of NPKS fertilizers, recommended fertilizers plus 50% additional K and S and recommended fertilizers with 2 t/ha ash) were assigned in main plots and four combinations of soil management and mulching (Conventional flat, Conventional with straw mulching @ 3 t/ha, Bed planting, and Bed with straw mulching @ 3 t/ha) were kept in subplots with three replications. Rice straw mulch was used after wheat sowing, wheat straw mulch was applied after maize sowing. Rice was puddle transplanted without mulch. Crop varieties like BARI GOM 25, BARI Hybrid Maize 7, and BRRI Dhan 39 were used for wheat, maize and rice, respectively. Chemical analysis of soils after two years of experimentation and the response of component crops for the two cropping cycles indicated that straw mulching either on bed or flat soil was equally effective in preventing rapid development of soil salinity in the dryer periods and thereby resulted in better stand establishment contributing to higher spikes/m2 of wheat and ears/m2 of maize. Available nutrient contents in soil, especially P (Olsen), B and K were improved when straw much was applied in bed or flat plantings. Application of ash with recommended fertilizer was effective in improving grain yields of component crops as compared to other fertilizer treatments without ash. The highest grain yield of wheat and maize was achieved when recommended dose of fertilizers plus ash with straw mulching were applied either in bed or flat soil condition for both the years. Treatment effect was not noted on rice yield in the first year, however the residual effect of treatments and its combinations became significant in the second year. Like wheat and maize, rice yield positively increased by fertilizer+ ash and mulching. Straw mulch and ash application contributed to soil salinity mitigation, favoured crop establishment and improved the yields of component crops. Bangladesh J. Agril. Res. 41(1): 1-15, March 2016